The application of occlusion in clinical practice part 2: the taking of occlusal records. (2nd January 2019) - Mehta, Shamir; Banerji, Subir
Abstract : The second part of this series of three articles aims to consider the clinical steps when taking intra-occlusal records. It will also address the subsequent transfer of the outcomes onto an appropriate form of articulator. CPD/Clinical Relevance: The clinical steps to record the various intra-occlusal positions and their rationale are important to appreciate when undertaking rehabilitation or study of the stomatognathic system (SGS).